A Study on Fundus changes in Pregnancy-induced hypertension: A Four-year Observation - Pandu Rangaiah, Elluru; Gangisetty, Madhavi Latha; K, Sandhya; A, Latha; Syed, Meena (Indonesian Vitreoretinal Society, 2021)
Introduction: Hypertensive disorders complicate 5-10% in all pregnant and together form the deadly triad and hemorrhage and heart disease that contribute greatly to maternal morbidity or mortality. This study aims to identify retinal changes in pregnancy-induced hypertension and analyze the association between retinal changes and hypertension severity. Method: A total of 100 pregnant admitted with pregnancy-induced hypertension(PIH) were included. Patients with pre-existing hypertension, diabetes mellitus, and renal diseases were excluded from the study. The vision, anterior segment, and Fundus were examined. Result: Higher number of PIH were recorded in the 21-30 years age group. Fifty-four pregnant women suffered from mild preeclampsia, 40 pregnant women with severe preeclampsia, and six pregnant women with eclampsia with seizures. 41% of pregnant had normal fundus, and 24% of pregnant had hypertensive retinopathy. Whereas grade 2,3, and 4 retinopathy was observed in 22%, 6%, and 2% of pregnant women. Two percent of pregnants had macular edema, and 3% had central serous retinopathy. No association was observed between the fundus findings with age/gravida. Whereas a significant positive correlation was observed between the fundus findings and hypertension severity (P < 0.001). Conclusion: Overall, 54% of pregnants were recorded with hypertensive retinopathy. A positive correlation was observed between fundus changes with the hypertension severity. This study reports the importance of routine fundus examination in pregnant with hypertension. Retinal change during pregnancy is an important indicator to decide the pregnancy termination or any other opt.